Influência do método de preparação e da adição de promotores em catalisadores do tipo FeCo aplicados a oxidação do estireno - Oliveira, Ana Paula Saraiva de (2018)
Nanosized FeCo-based solids were prepared by co-polymer assisted co-precipitation (CP), sol-gel (SG), nanocasting (NC) and chemical modification (CM) procedures. The effects of the addition of promoters in FeCo such as Sn, Mo or Cu was also investigated. The catalysts were characterized with XRD, Raman spectroscopy, TEM, chemical analyses, EPR and SEM-EDS and their catalytic performances for styrene oxidation in the presence of hydrogen peroxide were evaluated. Among of these solids prepared by four different methods, the catalyst prepared by the NC and CM procedures allowed to achieve a partial incorporation of the Sn into the FeCo matrix forming a very active phase, namely Heusler alloy. This was ascribed to the high initial dispersion of Sn as promoter into the FeCo matrix, which led to available FeCoSn particles well dispersed and stable on the catalyst surface. In the case of incorporating Mo or Cu to the nanosized FeCo catalyst, a poor stability towards leaching was observed, when operating under the same reaction conditions. Cu was much less active than both Sn and Mo, mainly leading to acetophenone, ethylbenzene, 2-phenyl ethanol, 2-phenyl acetic acid and 2-phenyl acetaldehyde products. The best catalytic results under the optimized reaction conditions, especially at 50oC and styrene/H2O2 ratio of 1 were achieved with nanosized FeCoSn reaching a conversion of ca. 70% and selectivity for aldehydes of ca.27% and the selectivity for the condensation products was 29%.